Antimicrobial susceptibilities and mechanisms of resistance of commensal and invasive Mycoplasma salivarium isolates - Xiao, Li; Totten, Arthur H.; Crabb, Donna M.; Atkinson, Thomas Prescott; Waites, Ken B. (Frontiers in Microbiology, 2022)
Mycoplasma salivarium, an oral commensal organism, can cause severe invasive infections in immunocompromised individuals. Currently there is no treatment guidance for such infections. We performed antimicrobial susceptibility tests on 39 commensal and invasive M. salivarium isolates and investigated the mechanisms of antimicrobial resistance. Clindamycin was the most active agent [minimum inhibition concentration (MIC) range: 0.004 – 128 mg/L, MIC50 = 0.031 mg/L, MIC90 = 0.125 mg/mL)], followed by tetracycline and levofloxacin. All isolates were resistant to erythromycin (MIC ≥ 4 mg/L) due to the presence of 2057A (Escherichia coli numbering) in 23S rRNA. Three isolates with elevated clindamycin MICs (≥ 8 mg/L) harbored A2058T/G mutations in 23S rRNA gene; four sequential isolates from one patient developed C2611T and A2059G mutations accompanying the increase of clindamycin MICs. Five isolates with elevated tetracycline MICs (≥ 4 mg/L) had mutations in 16S rRNA gene (A965G/T, G966T, or A967C/T) and one of them harbored TetM. Nine isolates with elevated levofloxacin MICs (≥ 4 mg/L) had one or more mutations in gyrA, gyrB, parC or parE. Susceptibility breakpoints for clindamycin, tetracycline and levofloxacin were suggested to be ≤ 0.125, ≤ 2, and ≤ 2 mg/L, respectively. Antimicrobial resistance was documented in 12 (34.3%) non-duplicate isolates, of which 10 were invasive. Levofloxacin resistance was most frequent (25.7%). Multi-drug resistance was also observed (14.3%). This study demonstrates the frequent occurrence of antimicrobial resistance in M. salivarium, emphasizing the need for culture and susceptibility testing to guide antimicrobial therapy.